2015
DOI: 10.1080/13557858.2014.995155
|View full text |Cite|
|
Sign up to set email alerts
|

Immigration, ethnicity, and avoidable mortality in Canada, 1991–2006

Abstract: Immigrants overall and the selected ethnicities enjoy an advantage over nonimmigrants in avoidable mortality. However, for certain causes of death especially ischemic heart disease mortality among South Asian women, immigrants appeared worse-off than nonimmigrants. The results suggest differential access to and use of health services, differences in protective health-related behavior, and the healthy immigrant effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 57 publications
3
22
0
1
Order By: Relevance
“…An exception to the female mortality advantage was identified for causes of death amenable to only medical care and public health, which contrasted findings for immigrants and long-term residents in a larger Canadian study. 12 Specifically, for causes amenable to medical care, we found higher age-adjusted mortality rates among female immigrants compared with male immigrants and among female long-terms residents compared with male long-term residents. This finding may illustrate persistent barriers for female immigrants around access and usage of primary care services in Ontario.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…An exception to the female mortality advantage was identified for causes of death amenable to only medical care and public health, which contrasted findings for immigrants and long-term residents in a larger Canadian study. 12 Specifically, for causes amenable to medical care, we found higher age-adjusted mortality rates among female immigrants compared with male immigrants and among female long-terms residents compared with male long-term residents. This finding may illustrate persistent barriers for female immigrants around access and usage of primary care services in Ontario.…”
Section: Discussionmentioning
confidence: 69%
“…11 In a recent study, the immigrant health advantage was shown to extend partially to avoidable mortality, in that mortality rates from several preventable and treatable causes were estimated to be lower among immigrants compared with non-immigrants. 12 In contrast to their health advantage, recent research has shown an income gap between immigrants and Canadian-born residents. 13 Recent immigrants were 2.6 times more likely to be classified as low-income, relative to non-immigrants, 13 and the gap has been relatively unchanged from the year 2000.…”
Section: Introductionmentioning
confidence: 99%
“…With these linked-data, it is possible to analyze all-cause mortality differences according to several socioeconomic factors (Wilkins et al 2008;Mustard et al 2013), in particular, place of birth (Omariba et al 2014;Omariba 2015) and ethnic origin or Aboriginal identity (Tjepkema et al 2009(Tjepkema et al , 2010(Tjepkema et al , 2012a, as well as cause-specific mortality differences by occupation and skill level (Mustard et al 2010;Tjepkema et al 2013b), by educational attainment (Tjepkema et al 2012b), and by income level (Tjepkema et al 2013a). In most cases, the studies find a gradient in mortality favouring persons of higher SES (with skilled jobs, higher levels of education, higher incomes, etc.…”
Section: Socioeconomic Inequalities In Healthmentioning
confidence: 99%
“…The recent studies [80][81][82] demonstrated that ethnicity was associated with poorer symptom recognition, and protective health-related behaviors that lead to delay in seeking care. The findings of this systematic review confirm the association between ethnicity and longer delay time.…”
Section: Association Between Ethnicity and Time Taken To Seek Care Fomentioning
confidence: 99%